Standards and Codes : Implementing the Fund's Medium-Term Strategy and the Recommendations of the 2005 Review of the Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper informs Executive Directors of the operational changes that are being made to the Fund's work on Standards and Codes, to implement the Fund's Medium-Term Strategy (MTS) and the recommendations of the 2005 IMF-World Bank review of the Standards and Codes Initiative. The changes aim at improving (i) the country coverage and prioritization of Reports on the Observance of Standards and Codes (ROSCs) to make more efficient use of resources, (ii) the integration of ROSCs with Fund surveillance and technical assistance, for a better use of ROSC findings and greater support of reform efforts, and (iii) the clarity and timeliness of ROSCs. The paper focuses on the actions that are being taken and does not elaborate on the rationales for the corresponding recommendations, which were discussed by Directors in the context of the MTS and 2005 Review. The actions being taken are summarized in Table 1. Many of the actions do not apply to ROSCs carried out under the aegis of the Financial Sector Assessment Program (FSAP), which are typically subject to a separate set of procedures under the FSAP, or to financial sector ROSCs of Offshore Financial Centers, which are conducted separately. According to the proposals in the MTS, the next review of the Standards and Codes Initiative would take place in 2010.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; ROSC; ROSCS